2018
DOI: 10.1111/apa.14669
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire showed that Swedish paediatric clinics complied well with the revised European guidelines for diagnosing coeliac disease

Abstract: Aim In 2012, revised criteria for diagnosing childhood coeliac disease were published by the European Society for Paediatric Gastroenterology, Hepatology and Nutrition and incorporated into the revised Swedish guidelines the same year. These made it possible, in certain cases, to diagnose coeliac disease without taking small bowel biopsies. This survey assessed the extent to which the new guidelines were implemented by Swedish paediatric clinics two years after their introduction. Methods In October 2014, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This conclusion is corroborated by a 2019 questionnaire study that found that 86% of the participating clinics avoided endoscopy in children presenting with symptoms typical for CD and highly positive serology. 47 We therefore urge caution when interpreting the incidence data of children beyond 2012. Also, this may, in part, explain the decreasing overall incidence of CD observed 2013-2015.…”
Section: Coeliac Diseasementioning
confidence: 99%
“…This conclusion is corroborated by a 2019 questionnaire study that found that 86% of the participating clinics avoided endoscopy in children presenting with symptoms typical for CD and highly positive serology. 47 We therefore urge caution when interpreting the incidence data of children beyond 2012. Also, this may, in part, explain the decreasing overall incidence of CD observed 2013-2015.…”
Section: Coeliac Diseasementioning
confidence: 99%